Linkage and mapping of quantitative trait loci associated with angular leaf spot and powdery mildew resistance in common beans - Bassi, Denis (Genet Mol Biol, 2017)
Angular leaf spot (ALS) and powdery mildew (PWM) are two important fungi diseases causing significant yield losses in common beans. In this study, a new genetic linkage map was constructed using single sequence repeats (SSRs) and single nucleotide polymorphisms (SNPs), in a segregating population derived from the AND 277 x SEA 5 cross, with 105 recombinant inbred lines. Phenotypic evaluations were performed in the greenhouse to identify quantitative trait loci (QTLs) associated with resistance by means of the composite interval mapping analysis. Four QTLs were identified for ALS resistance. The QTL ALS11(AS), linked on the SNP BAR 5054, mapped on chromosome Pv11, showed the greatest effect (R(2) = 26.5%) on ALS phenotypic variance. For PWM resistance, two QTLs were detected, PWM2(AS) and PWM11(AS), on Pv2 and Pv11, explaining 7% and 66% of the phenotypic variation, respectively. Both QTLs on Pv11 were mapped on the same genomic region, suggesting that it is a pleiotropic region. The present study resulted in the identification of new markers closely linked to ALS and PWM QTLs, which can be used for marker-assisted selection, fine mapping and positional cloning.